Analisis Faktor-faktor yang Memengaruhi Pendapatan Usahatani Cabai Merah di Kecamatan Wuluhan Kabupaten Jember: Analysis of Factors Affecting Red Chili Farming Income in Wuluhan District, Jember Regency - Eliyatiningsih, Eliyatiningsih; Pertami, Rindha Rentina Darah; Salim, Abdurrahman; Erdiansyah, Iqbal (Gontor Agrotech Science Journal, 2025)
Red chilies remain a leading commodity in the horticultural sub-sector and deserve to continue develop. Many efforts have been made to increase red chili production and productivity through various cultivation techniques. This increased production is expected to increase farmers' incomes. This study aims to analyze the income of red chili farmers in the central area of Jember Regency and the factors that influence it. The study was conducted in Wuluhan District, Jember Regency, with 50 farmers as respondents and using a questionnaire. The analysis used a farm analysis to calculate the income of red chili farmers. Meanwhile, to determine the factors affecting farmer income, multiple linear regression analysis was used. Based on the results of the farm analysis, it was found that the income of red chili farmers was IDR. 43,196,607/hectare/planting season. The results showed that red chili farming income was significantly influenced by production, labor costs, and the selling price of red chili. Meanwhile, other factors such as land area, farming experience, fertilizer costs, and pesticide costs did not have a significant impact. Keywords: red chili, income, farming